The Portrayal Of Masculinity/ Feminity Between Malaysian And Australian University Websites - Jano, Zanariah; Md Noor, Shuhaida (2015)
This paper analyzed web features which were applicable to a cultural dimension namely masculinity/feminity which contributed to cultural understanding and assisted web designers in customizing the websites to a specific culture. Quantitative content analysis was utilized through a t-test and discriminant analysis. 60 samples of websites were selected from Malaysian and Australian universities. Predictor variables were “Use a fluid layout”, “Pop-ups”, “Homepage length”, “Use site map”, “Use simple background image”, “Use of flash” and “Highlight critical data”.The findings yielded that there was a relationship between the masculinity/feminity cultural dimension and features of website usability of different countries. Malaysian university websites tend to have lower masculinity index. The results of Discriminant analysis also confirmed that Malaysian university websites and Australian university websites differed significantly on a linear combination of seven variables of masculinity/feminity. Hence, the masculinity/feminity dimension is a factor to consider in ensuring the usability of websites of different countries. This research also suggests that localisation is still important in terms of university web marketing. Hence, the web is not a culturally neutral medium, but they reflect the cultural environment that surrounds the developers. This study is beneficial for web policy makers and web designers of universities in providing a guide in terms of integrating cultural values for specific cultures. Future research should examine other cultural dimension in universities of other countries to gain more insights into the relationship of culture and university web usability